Hemocompatible tissue-engineered vascular grafts using adult mesenchymal stem cells. (March 2018) - La, Anh; Tranquillo, Robert T.
Abstract: Vascular tissue engineering can now produce compliant and durable vascular grafts to address limited supply of autologous vessel grafts for patients with coronary artery disease. Due to the demand for an anti-thrombogenic luminal surface, mesenchymal stem cells (MSCs) have been investigated for their potential to differentiate into an endothelial phenotype. This can be done through several types of chemical and biomechanical stimulation. Adipose-derived MSCs are of particular interest because they present an autologous source of sufficient MSCs to seed a monolayer onto the lumen of a typical coronary bypass graft. This review provides an overview of recent developments in endothelial differentiation methods of MSCs and main findings, as well as perspectives on future research. Highlights: Vascular tissue engineering can now produce compliant and durable vascular grafts. Endothelial cells confer hemocompatibility of native blood vessels. Chemical and biomechanical stimulation induces endothelial differentiation of MSCs.